O Direito à dedução do IVA dos sujeitos mistos e seus reflexos - Cardoso, Daniela Sousa (2022)
The present study is about the Value Added Tax (VAT) and, more concretely, about the application of the VAT law regime applied to mixed taxable persons, namely in the cases associated with the manipulation of active operations e its deduction percentage. In this context, some holdings became more interesting for our study because of, in general, its mixed taxable persons, this is, taxable persons that use inputs related, at the same time, with activities that give the right of the deduction of the supported VAT and activities that do not give that deduction right. This problematic constitutes one of the tax mechanisms with higher complexity of application which originates other rules interpretation and application problems in the right of deduction in the EU and, internally, in each Member State (MS), creating some differences between companies of each state. In Portugal the regime applied to some holdings, which are mixed VAT taxable persons, has been clarified in consequence of different litigations between the taxable persons and the Fiscal Administration, which pushed them to the Court of Justice of the European Union (CJEU). In the sequence of the interpretation defended by the CJEU and the interpretation of those rules there is now a bigger unanimity. Even so, despite its more uniform interpretation, there remains a significant margin of discretion on the practical application of the right to deduction, whereby, it conflicts, sometimes, with the equality and neutrality principles, which are important principles for the VAT system function on EU. In the beginning of the VAT use in Portugal, the Portuguese Fiscal Administration didn’t admit other method than the one of the deduction percentage (pro-rata) for the VAT deduction for mixed taxable persons. However, this was never the CJEU understanding, which considered the pro-rata method of residual application, to be used only in operations that give the right of deduction and in operations that don’t give that right, since, if used indistinctively, this method can originate severe taxation and competitivity distortions. Therefore, the community jurisprudence allows the application of the actual affectation method, that by establishing a connection of each productive input to the operation where it was used permits higher accuracy and more neutrality on the tax deduction. The analysis of this problematic will allow to alert the VAT taxable persons in this reality, so they avoid the errors, the involuntary unfulfillment and other penalties. We will finalize this study by proposing solutions to fix undue deduction situations associated with the subject in analysis.